Sinensetin attenuates hepatic ischemia-reperfusion injury through suppressing GRP78/CHOP-mediated endoplasmic reticulum (ER) stress in mice - Yihong Yang; Guanghua Xiong; Huangqi Shi; Yulin Peng; Jinghong Liu; Yaxuan Jiang; Min Lu; Hongbo Liu; Yong Liu (Frontiers in Pharmacology)
ObjectiveHepatic ischemia-reperfusion injury (HIRI) frequently occurs as a complication in liver surgeries, which significantly impacting patient outcomes. Sinensetin (SEN) is a plant-derived polymethoxylated flavone with anti-inflammatory and anti-oxidative activities. However, the hepatoprotective effect of sinensetin in HIRI pathogenesis have not been fully explored.MethodsWe constructed the HIRI model in mice, with blood and liver samples collected at 6 and 24 h after reperfusion to evaluate liver injury. We also evaluated the protective effect of sinensetin in mice liver I/R injury through histopathological observation, enzyme activity, immunofluorescence, Western blot, molecular docking, and molecular pharmacology experiments.ResultsIn our study, we have successfully established the mouse HIRI injury model, and the liver function indicators such as ALT, AST and LDH were significantly increased in the HIRI model group, while SEN pretreatment could lead to a significant decrease in these enzymatic activities, especially perfusion at 6 h. In addition, hepatocytic necrosis and lipid deposition were significantly improved under SEN pretreatment conditions compared to the HIRI group alone. Meanwhile, HIRI can significantly increase the expression of genes related to liver injury and inflammation, while SEN pretreatment can lead to a concentration-dependent decrease in these genes. Besides, the level of liver apoptosis and apoptosis-related genes such as BAX and Bcl-2 were significantly reduced especially in the high concentration SEN pretreatment group, and antioxidant enzyme activities such as CAT and GSH-Px also showed similar changes. Moreover, the HIRI model and SEN pretreatment could lead to dynamic changes in key genes involved in endoplasmic reticulum (ER) stress signaling, while the expression and distribution of GRP78 and CHOP proteins in liver cells also showed significant decrease in HIRI + L-SEN and HIRI + H-SEN groups. Molecular docking simulation showed theoretical binding between SEN-GRP78 and SEN-IRE1α in three-dimensional structures. Ultimately, the use of 4-PBA to pharmacologically inhibit ER stress may substantially reduce liver damage caused by HIRI in mice.ConclusionTaken together, our results suggested that sinensetin could alleviate HIRI injury through suppressing GRP78/CHOP-mediated ER stress, which may provide a novel therapeutic strategy for treating liver ischemia-reperfusion injury in clinical practice.